2017
DOI: 10.3389/fnhum.2017.00028
|View full text |Cite
|
Sign up to set email alerts
|

Vibrotactile Discrimination Training Affects Brain Connectivity in Profoundly Deaf Individuals

Abstract: Early auditory deprivation has serious neurodevelopmental and cognitive repercussions largely derived from impoverished and delayed language acquisition. These conditions may be associated with early changes in brain connectivity. Vibrotactile stimulation is a sensory substitution method that allows perception and discrimination of sound, and even speech. To clarify the efficacy of this approach, a vibrotactile oddball task with 700 and 900 Hz pure-tones as stimuli [counterbalanced as target (T: 20% of the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 129 publications
2
6
0
4
Order By: Relevance
“…The overall rather late P300 deflection in the cap as well as the fEEGrid data is in line with previous vibrotactile oddball reports (e.g. [35,36]).…”
Section: Event-related Potentialssupporting
confidence: 92%
“…The overall rather late P300 deflection in the cap as well as the fEEGrid data is in line with previous vibrotactile oddball reports (e.g. [35,36]).…”
Section: Event-related Potentialssupporting
confidence: 92%
“…Furthermore, they showed larger responses to tactile motion in the right posterior superior temporal sulcus (pSTS), pointing to crossmodal plasticity as a result of the early auditory deprivation. This is in accordance with findings from González-Garrido et al (2017) , who presented an oddball task with vibrotactile stimuli to early deaf participants ( n = 14; mean age = 21.96 years, SD = 6.63 years) and matched hearing controls ( n = 14; mean age = 21.93 years, SD = 5.02 years). Except for one native signer, all deaf participants acquired Mexican Sign Language (LSM) after the age of 7 years.…”
Section: Subsections Relevant For the Subjectsupporting
confidence: 91%
“…Computer-based auditory training program was found to be effective and can improve the overall hearing abilities [25]. Gonzalez-Garrido et al [6] found that training increases P300 amplitudes in both normal and deaf patients. We also found similar properties of P300 waves and its increase with education and perception with the literature.…”
Section: Discussionmentioning
confidence: 99%